The A736V TMPRSS6 Polymorphism Influences Hepatic Iron Overload in Nonalcoholic Fatty Liver Disease - Valenti, Luca; Rametta, Raffaela; Dongiovanni, Paola; Motta, Benedetta M.; Canavesi, Elena; Pelusi, Serena; Pulixi, Edoardo A.; Fracanzani, Anna L.; Fargion, Silvia (PLOS ONE, 2012)
Background & Aims Hepatic iron accumulation due to altered trafficking is frequent in patients with nonalcoholic fatty liver disease (NAFLD), and is associated with more severe liver damage and hepatocellular carcinoma. The p.Ala736Val TMPRSS6 variant influences iron metabolism regulating the transcription of the hepatic hormone hepcidin, but its role in the pathogenesis of iron overload disorders is controversial. Aim of this study was to evaluate the whether the TMPRSS6 p.Ala736Val variant influences hepatic iron accumulation in a well-characterized series of Italian patients with histological NAFLD. Methods 216 patients with histological NAFLD. TMPRSS6 and HFE variants were assessed by allele specific PCR, liver histology by the NAFLD activity score and Perls' staining for iron. Results Homozygosity for the p.736Val allele previously linked to higher hepcidin did not influence transferrin saturation (TS), but was associated with lower hepatic iron stores (p = 0.01), and ferritin levels (median 223 IQR 102–449 vs. 308 IQR 141–618 ng/ml; p = 0.01). Homozygosity for TMPRSS6 p.736Val was nearly associated with lower ballooning (p = 0.05), reflecting hepatocellular damage related to oxidative stress. The influence of TMPRSS6 on hepatic iron accumulation was more marked in patients negative for HFE genotypes predisposing to iron overload (p.Cys282Tyr + and p.His63Asp +/+; p = 0.01), and the p.736Val variant was negatively associated with hepatic iron accumulation independently of age, gender, HFE genotype, and beta-thalassemia trait (OR 0.59, 0.39–0.88). Conclusions The p.Ala736Val TMPRSS6 variant influences secondary hepatic iron accumulation in patients with NAFLD.